PHENOTYPIC CHARACTERISTICS OF SWAMP BUFFALOES OF MANIPUR* (Indian Journal of Animal Production and Management, 2013)
An investigation was carried out to study certain phenotypic characteristics of swamp type buffaloes of Manipur in 2009 - 2010. Average body weight, body length, heart girth, height at withers, pouch girth and length of tail were found to be 223.06 ± 6.70 kg, 98.96 ± 1.16, 142.60 ± 1.60, 108.85 ± 0.92, 149.29 ± 1.61 and 46.78 ± 0.95 cm respectively. Significant effect was observed on all these phenotypic characteristics due to age group and sex while type exerted no significant effect on the above characteristics. All these phenotypic characteristics exhibited an increasing trend with the advancement of age. Higher values were recorded in males than the females on all these phenotypic characteristics.
Keywords: Swamp buffalo; Manipur; Semi-wild